Pulsed wide-spectral phototherapy of soft tissue gunshot wouds - V. V. Bagrov; A. N. Bobin; V. A. Bobylev; L. Y. Volodin; D. V. Davydov; A. S. Kamrukov; A. V. Kondratiev; M. V. Nesterova; M. S. Pecherskaya; A. V. Fateev; M. A. Shchedrina; N. B. Esaulenko (Biomedical Photonics, 2025)
A new method has been proposed for the treatment of gunshot wounds complicated by nosocomial microflora. The method is based on the treatment of wounds with high-intensity pulsed optical radiation of a continuous spectrum in the wavelength range from 200 to 1100 nm. A pulsed xenon lamp is used as a radiation source.  The effect of high-intensity pulsed wide-spectrum optical radiation and low-intensity continuous UV radiation with a maximum at a wavelength of 272 nm and a half-width of the spectrum of 12 nm on the course of the wound process in a gunshot injury was compared. It has been shown that the effect of such radiation on tissues with signs of purulent-inflammatory process provides an antibacterial effect and stimulates tissue regeneration. At the same time, high-intensity wide-spectral optical radiation has a more pronounced anti-inflammatory effect and contributes to the earlier development of tissue regeneration compared with low-intensity narrow-spectrum UV radiation. However, the use of high-intensity optical radiation requires an individual dosage for each phase of the wound process.